The patient compliance regarding of eye-care information after cataract operation - Ahmad, Che Hasmah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2006)
A long term observation study has been done by observing the level of patient compliance concerning eye-care after cataract surgery and the right technique of eye drop instillation among patients that perform cataract surgery at HUSM, Kelantan. Level of compliance is the main factors that determine effectiveness of visual treatment after cataract surgery. This is important in order to avoid any complications that can cause permanent blindness. To evaluate patient's compliance to eye-care and right technique of installation of eye drop among patients that has performed cataract surgery and the influencing factors. There were 51 patients that underwent cataract surgery were attended first session of appointment after cataract surgery from December 2005 to January 2006 at Ophthalmology Clinic, HUSM, were interviewed by using research question. All of them had given eye-care information for post cataract operation and instruction of instillation of eye drop before discharge. Data were collected and analyzed by using descriptive test, Independent Samples Test and ANOVA for mean score, where the reading P<0.05 is considered significant. Result of the study showing the level of compliance of patient to eye-care after cataract surgery are high, including the aspects of hygienic, safety, diet, avoidance of vibration and pressure. Significant factors are age, race, educational level and work. Else, 13 out of 51 samples chose to instill eye drop independently and 38 samples chose to be dependent, the significant factor for the right technique of instillation of eye drop is age. From the results, although it shows the level of compliance and the instillation techniques of eye drop higher, but it should be increased by observing the group of patients having problems and the influencing factors. Thus, efforts to overcome the factors must be observed by all the health members that parties in order to achieve the success of the treatment.